2017
DOI: 10.1002/bdr2.1113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence trends of selected major birth defects: A multi‐state population‐based retrospective study, United States, 1999 to 2007

Abstract: No significant trends in prevalence were identified for most birth defects. Gastroschisis prevalence increased significantly among NHW and NHB mothers <20 years of age, with the greatest increases in NHB mothers. Prevalence of Down syndrome among NHB mothers ≥35 years also increased slightly. Stratified results may suggest avenues of research in birth defect etiology and in evaluating prevention efforts. Birth Defects Research 109:1442-1450, 2017.© 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
35
3
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 24 publications
(35 reference statements)
7
35
3
3
Order By: Relevance
“…Our IHPS prevalence estimates differ from another US study which reported an overall prevalence (per 10,000 live births) of 15.8 (95% CI = 15.61, 16.04) from 1999–2007, but no significant change in prevalence during this birth period (St Louis et al, ). Although our study and that of St Louis et al () included mostly overlapping time frames and data from multiple surveillance programs in the US, only six programs (AZ, CO, FL, GA, NY, and TX) overlapped. Differences in the racial/ethnic distributions of cases and live births included between the two studies may have contributed to the variable findings for IHPS prevalence.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our IHPS prevalence estimates differ from another US study which reported an overall prevalence (per 10,000 live births) of 15.8 (95% CI = 15.61, 16.04) from 1999–2007, but no significant change in prevalence during this birth period (St Louis et al, ). Although our study and that of St Louis et al () included mostly overlapping time frames and data from multiple surveillance programs in the US, only six programs (AZ, CO, FL, GA, NY, and TX) overlapped. Differences in the racial/ethnic distributions of cases and live births included between the two studies may have contributed to the variable findings for IHPS prevalence.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous review has suggested an increased predisposition for IHPS in populations living in temperate regions of North America and Western Europe compared to those in tropical countries (Spicer, 1982). Reported prevalence estimates (per 10,000 live births) for IHPS range from 17 to 50 in the United States (US) (Applegate & Druschel, 1995;Markel, Proctor, Ying, & Winchester, 2015;Schechter, Torfs, & Bateson, 1997;St Louis et al, 2017) and Western Europe (de Laffolie, Turial, Heckmann, Zimmer, & Schier, 2012;Hedback, Abrahamsson, Husberg, Granholm, & Oden, 2001;O'Donoghue et al, 1993;Pedersen et al, 2008;Sommerfield et al, 2008;Sule, Stone, & Gilmour, 2001). Some populations in Western Europe have reported declines in IHPS prevalence across different birth periods from the 1980s through the 2000s, although others have not (de Laffolie et al, 2012;O'Donoghue et al, 1993;Pedersen et al, 2008;Sommerfield et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall prevalence estimates presented in this data brief for both gastroschisis and omphalocele are consistent with those previously reported in the literature (Mai et al, ; Springett et al, ; St Louis et al, ; Vo & Langlois, ; Vu et al, ). Variations in prevalence by maternal race/ethnicity, maternal age at delivery, maternal prepregnancy BMI, infant sex, and infant birth weight also largely reflect previously reported estimates (Anderson et al, ; Kirby, ; Kirby et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…We disagree with Dr. Harcombe. One obvious reason why the case-control design is absolutely appropriate for our research objective is that NTDs are rare in the general population, with spina bifida for example affecting only 3 per 10,000 births in the United States (St Louis et al, 2017). In the context of such a rare outcome, the case-control design offers significant advantages over a cohort study in statistical efficiency (and consequently in study resources) by including eligible cases from a well-defined base population, and sampling only a subset of that same base population as controls (Rothman, Greenland, & Lash, 2008a).…”
mentioning
confidence: 99%